Role of microRNAs in allergic asthma. Issue 2 (April 2015) - Perry, Mark M.; Adcock, Ian M.; Chung, Kian Fan
<x xml:space="preserve">Abstract</x> Purpose of review MicroRNAs (miRNAs) modulate gene transcription in response to environmental stressors and other stimuli. A role for miRNAs in inflammation and immunity has been demonstrated and further evidence suggests that miRNAs also play a role in allergic asthma. Recent findings Studies investigating the differential expression of miRNAs in biological fluids between asthma patients and controls have been published, as have their role in immune cell subsets. Further development of miRNAs in therapy has been addressed. miRNA-146a has been implicated in autoimmunity and allergic inflammation and miRNA-155 in the development of atopy. Targeting of miRNA-1 and miRNA-145 has been used to inhibit lung inflammation in mouse models of asthma. Although these recent findings need to be confirmed, miRNAs may prove to be useful as potential biomarkers of disease. However, their use as therapeutic targets in the lung remains unclear. Summary There may be a potential role for using circulating miRNAs as biomarkers of disease status or response to therapy. The use of miRNAs as asthma therapy remains to be determined.